2021
DOI: 10.3389/fmed.2021.688535
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Lymph Node Staging Schemes for Predicting Survival Outcomes in Node-Positive Endometrioid Endometrial Cancer Patients

Abstract: Objective: To compare the prognostic predictive performance of six lymph node (LN) staging schemes: American Joint Committee on Cancer (AJCC) N stage, number of retrieved lymph nodes (NRLN), number of positive lymph nodes (NPLN), number of negative lymph nodes (NNLN), lymph node ratio (LNR), and log odds of positive lymph nodes (LODDS) among node-positive endometrioid endometrial cancer (EEC) patients.Methods: A total of 3,533 patients diagnosed with node-positive EEC between 2010 and 2016 from the Surveillanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…We chose age, race, grade, histology, T stage, tumor size, and LODDS from the univariate Cox analysis (all p < 0.05). Surprisingly or not, 09 FIGO stage was not able to discern the patients with optimal overall survival from those who had not ( p = 0.062), which was in accordance with the previous studies ( 9 , 13 , 14 , 16 , 18 ). Multivariate analysis was sequentially performed to identify the age, grade, T stage, tumor size, and LODDS as the independent risk factors for the survival outcomes in stage IIIC EC patients with ART alone ( Table 2 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We chose age, race, grade, histology, T stage, tumor size, and LODDS from the univariate Cox analysis (all p < 0.05). Surprisingly or not, 09 FIGO stage was not able to discern the patients with optimal overall survival from those who had not ( p = 0.062), which was in accordance with the previous studies ( 9 , 13 , 14 , 16 , 18 ). Multivariate analysis was sequentially performed to identify the age, grade, T stage, tumor size, and LODDS as the independent risk factors for the survival outcomes in stage IIIC EC patients with ART alone ( Table 2 ).…”
Section: Resultssupporting
confidence: 89%
“…It is noteworthy that rare pathological histology type was not included in this study, and we presented the histology type as type I (endometrioid cancer and adenocarcinoma) and type II consisting of serous cancer, carcinosarcoma, and clear cell cancer. The log odds of positive lymph nodes (LODDS), defined as log e [(number of positive LN + 0.5)/(number of negative LN + 0.5)], was calculated to represent the LN status given that our previous studies have demonstrated that LODDS was the optimal LN index to predict the survival probability for EC patients with LN metastases ( 13 , 14 ). X-tile software (version 3.6.1; Yale University, New Haven, CT, USA) was used to identify the best cutoff values for continuous variables including age, tumor size, and LODDS given the inconsistency of these cutoff values from previous research ( 8 , 15 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…evaluated the efficacy of six schemes in predicting the survival after endometrioid endometrial cancer: LODDS, AJCC N staging, the number of lymph nodes examined, the number of positive lymph nodes, the number of negative lymph nodes, and the lymph node ratio. The results demonstrated that LODDS was superior in prognostic assessment compared with AJCC N staging 27 . Currently, there are no studies that have used LODDS to predict the survival rate of endometrial clear‐cell carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Both the number of positive and negative lymph nodes are considered as evaluation metrics in LODDS, which has been demonstrated to be effective at predicting cancer prognosis in multiple studies. 7,25,26 For instance, Yang et al 27 evaluated the efficacy of six schemes in predicting the survival after endometrioid endometrial cancer: LODDS, AJCC N staging, the number of lymph nodes examined, the number of positive lymph nodes, the number of negative lymph nodes, and the lymph node ratio. The results demonstrated that LODDS was superior in prognostic assessment compared with AJCC N staging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation